Pelatihan Pengolahan Kotoran Hewan Menjadi Kompos Untuk Mendukung Praktik Pertanian Ramah Lingkungan Di Desa Sukadana Kabupaten Lombok Utara - Jayaputra, Jayaputra; Santoso, Bambang Budi; Jaya, I Komang Damar (Universitas Mataram, 2025)
This Community Service activity was carried out in Labangkara, Sukadana Village, Bayan District, North Lombok Regency, from July to November 2024, in collaboration with the Padi Subur farmer group. Agriculture in this village is dominated by dry land with low productivity and crop diversification. Farmers face challenges in cultivation that is not yet intensive and reliance on chemical inputs such as inorganic fertilizers, pesticides, and herbicides, which increase production costs and cause environmental pollution, threatening agricultural sustainability. On the other hand, livestock waste (cattle and goats) in this village has not been utilized, causing environmental impacts such as unpleasant odors from ammonia and hydrogen sulfide gases, as well as health risks. The aim of this activity was to provide knowledge and skills to farmer group members on making compost from livestock waste, to support crop diversification and sustainable agriculture. The approach used was the participatory action method, involving the community fully from planning to evaluation. The results showed a significant increase in participants' understanding, seen from their ability to explain the steps of compost making after the training. Participants' enthusiasm and active participation, both in discussions and independent practice, were also very high, indicating their great interest in managing animal waste into useful compost. This success confirms the effectiveness of interactive and practical training methods, as well as demonstrative methods, in increasing knowledge and learning motivation.